The Influence of Work Motivation, Work Facilities and Physical Work Environment on Employee Performance at The Jakarta City Industry and Trade Office - Fadjar Arief Perdana Putra; Herry Krisnandi; Kumba Digdowiseiso (Jurnal Syntax Transformation, 2024)
This study aims to analyze the effect of motivation, facilities and physical work on employee performance at the Jakarta City Industry and Trade Office. Types of Research Using Quantitative Techniques, Descriptive Methods and Data Analysis Methods Using Multiple Linear Regression Inferential Analysis and Using Primary Data in the form of Closed Questionnaires to 100 Respondents Assisted by Using the Statistical Product and Service Solution (SPSS) Version 23.0 program The results of the analysis in this study prove that the three variables of motivation, facilities and physical environment of work which certainly have a significant influence on the defenden variable is employee performance. From the results of this study expect the ministry to pay attention and evaluate employee performance in order to improve employee performance to be good and effective